Corruption in healthcare: a view from the pandemic - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Streltsov, Yevgen; Streltsov, Yevhen L.; Дуліба, Євгенія Володимирівна; Дуліба, Є. В.; Duliba, Yevheniia V.; Стрельцов, Євген Львович; Стрельцов, Є. Л.; Streltsov, Yevhen L.; Харченко, Вадим Борисович; Харченко, В. Б.; et al. (Newbury Park : SAGE Publishing, 2024)
Corruption in healthcare has become transnational and intersectoral in nature; leading countries around the world have become vulnerable and insufficiently prepared to address health crises. The article deals with topical issues of corruption in healthcare during the Covid-19 pandemic in public and private sectors. By comparing different ratings, we concluded that there is a correlation between the level of corruption and the average annual income of the respective state, the observance of human rights and democratic standards in the context of their response to the Covid-19 pandemic.
Duliba Y. Corruption in healthcare: a view from the pandemic / Y. Duliba, Y. Streltsov, V. Kharchenko et al. // Medico-Legal Journal. – Newbury Park : SAGE Publishing, 2024. – 92(1). – P. 43–45. Режим доступу: https://hdl.handle.net/11300/32303
Keywords: Covid-19 pandemic; corruption; public procurement; combatting corruption; healthcare system